The Complier Pays Principle : The Limits of Fiscal Approaches toward Sustainable Forest Management - Leruth, Luc (IMF Working Papers; Working Paper ;, 2000)
This paper examines the role and impact of taxation on sustainable forest management. It is shown that fiscal instruments neither reinforce nor substitute for traditional regulatory approaches. Far from encouraging more sustainable forest management, fiscal instruments such as an inappropriate tax policy can actually undermine it. The paper uses the arguments at the root of the Faustmann solution to draw conclusions on the incentives for sustainable tropical forest exploitation. The paper also proposes a bond mechanism as an alternative market-based instrument to encourage sustainable forest logging while reducing monitoring costs.